2018
DOI: 10.1017/s0022215118001846
|View full text |Cite
|
Sign up to set email alerts
|

Studying the result of underlay myringoplasty using platelet-rich plasma

Abstract: ObjectivePerforations of the tympanic membrane are treated with various surgical techniques and materials. This study aimed to determine the efficacy of platelet-rich plasma during underlay myringoplasty.MethodsThe study included 40 patients. Autologous platelet-rich plasma was applied in-between temporalis fascia graft and tympanic membrane remnant during underlay myringoplasty in group 1 (n = 20). The outcome was evaluated after three months and compared with group 2 (n = 20), a control group that underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Of the 34 nonrepetitive studies identified, eight studies [8][9][10][11][12][13][14][15] including 455 participants with different sizes of TM perforations were eligible for final selection after screening the full texts. These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 34 nonrepetitive studies identified, eight studies [8][9][10][11][12][13][14][15] including 455 participants with different sizes of TM perforations were eligible for final selection after screening the full texts. These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty. Among the seven studies in which the experimental groups received PRP three involved fat graft myringoplasty (FGM) [8,9,14], one used conchal perichondrium myringoplasty (PM) [13], and three involved temporalis fascia tympanoplasty (TFT) [10,12,15].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations